PENGEMBANGAN SUMBER DAYA APARATUR SIPIL NEGARA PADA KANTOR PEMBERDAYAAN MASYARAKAT DAN PEMERINTAHAN DESA KABUPATEN PARIGI MOUTONG - Agus Salim (Katalogis, 2018)
This study aims to identify and analyze the Civil Resource Development State Apparatus Empowerment At the agency office and village authorities, through a qualitative descriptive approach on the basis of opinion (Armstrong, 2006: 535), comprising: Pendidika, Training and Development. Based on the research and discussion hasi concluded that: Education, Human Resource development in terms of education has not run optimally it is because civil servants sispil that exist in the community Empowerment Board office and village government, because terkendalan costs, in terms of leadership is very supportive. Training has been going up because training is conducted under the provisions in force and every employee is entitled to participate for the sake of self-development and needs of office and duties. Development, also has been running with a maximum stay of willingness iut employees only for education and training. The development has not been implemented to the fullest because many employees who have work ability, work performance and an adequate education can notaccommodated for positions.